A Mentoring Network for Novice and Experienced Music Teachers: Concept, Design, Outcomes, and Recommendations. Issue 2 (February 2022) - Weimer, Kristina R.; Albert, Daniel J.
Two university music education faculty aimed to expand mentoring beyond a one-to-one relationship to a more collaborative approach by creating a year-long online mentoring network of experienced and novice music educators. The purpose of this article is to describe the network's structure and content, and discuss outcomes and recommendations based on participating teachers' perspectives and experiences. Network materials promoted discussion and reflection on various music teaching and learning topics; the sharing of strategies, ideas, and resources; and mutual support and encouragement. Participants discussed topics with direct application for their classes and shared rewarding teaching moments, student successes, positive assessment outcomes, and struggles with fatigue and lack of student engagement. They stated the network provided a supportive space that facilitated connection and reflection, empathetic feedback, and teaching strategy and resource suggestions. Recommendations included more active opportunities to engage with and build relationships with each other, synchronous activities via videoconferencing platforms, and more facilitator participation.